2017
DOI: 10.1590/2177-9465-ean-2017-0082
|View full text |Cite
|
Sign up to set email alerts
|

Does the spirituality of nurses interfere in the record of spiritual suffering diagnosis?

Abstract: Objectives: To assess the spirituality of nurses and relate it to personal characteristics, sector of activity, and spiritual practices; to analyze the influence of spirituality of nurses in the record of a "spiritual suffering" diagnosis. Methods: Quantitative cross-sectional study, using the World Health Organization's Quality of Life Instrument-Spirituality, Religion and Personal Beliefs Module (WHOQOL-SRPB). Results: 132 nurses were included and most of them were women (81.8%), married (56.8%), with an ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
0
5
0
9
Order By: Relevance
“…This corroborates findings in the literature that indicate that even if instruments exist to carry out the assessment of spiritual distress, its identification is often performed, or should be, based on the professionals' individual critical sense (19) . It is essential that nurses know how to incorporate spiritual practice in their practice, since they must act from a holistic perspective, not ignoring this dimension (20) .…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates findings in the literature that indicate that even if instruments exist to carry out the assessment of spiritual distress, its identification is often performed, or should be, based on the professionals' individual critical sense (19) . It is essential that nurses know how to incorporate spiritual practice in their practice, since they must act from a holistic perspective, not ignoring this dimension (20) .…”
Section: Discussionmentioning
confidence: 99%
“…However, terms of virtue indicators such as "Spirituality", "Empathy" and "Faith" were found and reflect the concern that these themes have on the person, which resumes the importance of developing nursing diagnoses and interventions based on these terms, once that the nurse seeks to find options that contribute to better control and a harmonious coexistence with the disease, since the negative physical, social and economic impacts perceived in the disease also cause consequences in the sense of life. In studies, the scenario of low frequency of psycho-emotional diagnoses in medical records has shown that care provided by nurses is still very much focused on a medical-centered model (37) . Therefore, it is necessary that nursing actions, based on their care instrument, give value to the issues surrounding the psychosocial experiences of individuals with chronic kidney disease and their approximation in their social support network, whether family or community.…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, ajudam também na ampliação da sensibilidade para perceber as necessidades espirituais dos pacientes (Dezorzi et al, 2008). Os profissionais de enfermagem estão preparados para identificar tais necessidades, mas primeiramente eles precisam estar preparados para identificar as suas próprias necessidades, e assim poder realizar as ações de cuidado espiritual para com o outro (Ienne et al, 2018). Azarsa et al (2015) apontam que o bem estar espiritual entre os enfermeiros está diretamente correlacionado ao aumentando da atitude positiva em relação à espiritualidade e ao cuidado espiritual na enfermaria de UTI.…”
Section: Bem-estar Espiritualunclassified
“…Azarsa et al (2015) apontam que o bem estar espiritual entre os enfermeiros está diretamente correlacionado ao aumentando da atitude positiva em relação à espiritualidade e ao cuidado espiritual na enfermaria de UTI. Corroborando com esta pesquisa, Ienne et al (2018) mostram que enfermeiros que apresentavam maior conexão espiritual em momentos difíceis lidam melhor com o estresse, sentem-se confortados e bem no dia-dia devido à contribuição da fé. Estes fatores estão relacionados com a vontade de conversar sobre espiritualidade com o paciente.…”
Section: Bem-estar Espiritualunclassified
See 1 more Smart Citation